Efforts to Increase Student Entrepreneurial Intentions Through the Project-Based Learning Learning Model - Jaenudin, Ahmad; Raharjo, Teguh Hardi; Astuti, Dwi Puji; Nuraini, Siti (Economic Education and Entrepreneurship Journal, 2023)
Knowledge of student entrepreneurship intentions is a fundamental impetus that is very important in understanding entrepreneurship in tertiary institutions. This study aims to determine the effectiveness of the project-based learning model in increasing student entrepreneurial intentions in economics and digital business learning. This research is quantitative research with an experimental research design. The sample in this study was 80 students. This study uses actual experiments because, in this design, the researcher can control all external variables that affect the course of the investigation. Data collection in this study used instruments in the form of questionnaires and documentation developed according to indicators and based on relevant theories. The results showed that the significance value of the t-test was 0.000. The significance value is less than 0.05, which means that H1 is accepted. This shows that there are significant differences in the entrepreneurial intentions of the experimental class as the class that uses the project-based learning model and the control class that uses the conventional model. Thus, implementing the project-based learning model in the experimental class significantly differs. This means that applying the project-based learning model in digital economics and business learning effectively increases student entrepreneurial intentions. ttable, which is equal to 1.985. This shows significant differences in the entrepreneurial intentions of the experimental class as the class that uses the project-based learning model and the control class that uses the conventional model. Thus, implementing the project-based learning model in the experimental class significantly differs. This means that applying the project-based learning model in digital economics and business learning effectively increases student entrepreneurial intentions. ttable, which is equal to 1.985. This shows that there are significant differences in the entrepreneurial intentions of the experimental class as the class that uses the project-based learning model and the control class that uses the conventional model. Thus, implementing the project-based learning model in the experimental class significantly differs. This means that applying the project-based learning model in digital economics and business learning effectively increases student entrepreneurial intentions.Keywords: Project Based Learning, Entrepreneurial IntentionDOI: http://dx.doi.org/10.23960/E3J/v6i1.8-14